The Effect of Capital Structure, Growth Company and Profitability on Value Company Moderated Good Corporate Governance (Gcg) and Sustainability Reporting (Study on Consumer Goods Industry Companies Listed on Idx 2020-2024) - Irvindha Sella Novelyna Handayani; Asep Risman (MAMEN: Jurnal Manajemen, 2026)
This study investigates the effects of capital structure, firm growth, and profitability on firm value, with Good Corporate Governance (GCG) and sustainability reporting as moderating variables. A quantitative approach was applied using secondary data from financial statements and sustainability reports of consumer goods companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. The sample was selected through purposive sampling, resulting in 15 firms and 75 firm-year observations. Panel data regression analysis was conducted using EViews software. The findings reveal that capital structure and firm growth positively and significantly affect firm value, while profitability does not show a significant influence. GCG moderates the relationship between capital structure and firm growth on firm value but fails to moderate the link between profitability and firm value. Sustainability reporting also moderates the relationship between capital structure and firm growth, yet does not moderate the effect of profitability. These results suggest that firm value in Indonesia’s consumer goods industry is driven more by strategic financing and growth decisions, reinforced by governance quality and sustainability disclosure, rather than short-term profitability. The study highlights the importance of integrating financial policies, governance mechanisms, and sustainability practices to enhance market perceptions of firm value.